The Role of Vehicle Insurance Products on the BPKB Pawn System at PT. Pawnshop CPS Rantau Prapat - Yuli Anisyah Hasibuan; Tri Inda Fadhila Rahma (Penerbit Jurnal Indonesia, 2022)
The sharia is a non bank financial institution that provides financing transactions and pawn services based on islamic is quran and hadist. The puposse of this study was to benefit and roles BPKB in motorized vechile pawn products in PT. Pegadaian CPS Rantau Prapat. The results of the study conclude that the mechanism of the vichel pawn prduct or called by trust product in PT. Pegadain CPS Rantau Prapat the costumers submints an aplication to the pawnshop by meeting then the pawnshop makes a sale and purchase to the dealer, the costumer submits proof of the owner of the motor vichle to the sharia pawnshop as collateral to carry out financing with trust products. In a trust transaction using a murabahah contract in buying and selling transaction and tasjili pawns so that the interest in the product is trustworthy, taken from down payment, maintenance cost, elaboration between practice in the field and a riview of Islamic Fatwa DSN-MUI.